Risk of cancer in psoriasis: a systematic review and meta‐analysis of epidemiological studies. (11th July 2013) - Pouplard, C.; Brenaut, E.; Horreau, C.; Barnetche, T.; Misery, L.; Richard, M.‐A.; Aractingi, S.; Aubin, F.; Cribier, B.; Joly, P.; Jullien, D.; Le Maître, M.; et al.
Abstract: The relationship between psoriasis and increased cancer risk is debated. The aim of this study was to evaluate if there is an increase in the background risk of cancer in psoriasis patients compared with the general population. A systematic literature search was performed on PubMed, Embase and Cochrane databases, using the keywords 'Psoriasis [Majr] AND Neoplasms', from 1980 to January 2012. Meta‐analysis was performed based on observational studies showing consistency in cancer risk assessment methods. Of the 1080 articles retrieved, 37 references were selected. There may be an increased risk of some solid cancers in psoriasis: respiratory tract cancer [standardized incidence ratio (SIR) = 1.52, 95% confidence interval (CI) 1.35–1.71], upper aerodigestive tract cancer (SIR = 3.05, 95% CI 1.74–5.32), urinary tract cancer (SIR = 1.31, 95% CI 1.11–1.55) and liver cancer (SIR = 1.90, 95% CI 1.48–2.44). The risk of non‐Hodgkin lymphoma appears slightly increased in psoriasis (SIR = 1.40, 95% CI 1.06–1.86). Psoriasis patients have an increased risk of squamous cell carcinoma (SIR = 5.3, 95% CI 2.63–10.71) and basal cell carcinoma (SIR = 2.00, 95% CI 1.83–2.20), whereas the risk of melanoma is not increased. There was a large heterogeneity in studies assessing cancer risk in psoriasis preventing from including all studies in meta‐analysis. This systematic literature review shows a small increased risk of some solid cancers in psoriasis, especially those linked to alcohol drinking and cigarette smoking. A higher risk of non‐melanoma skin cancers, especially squamous cell carcinoma, is shown, mainly due to previous exposure to 8‐methoxypsoralen‐ultraviolet‐A (PUVA), ciclosporin and possibly methotrexate.